Proceedings of the 2025 4th International Conference on Engineering Management and Information Science (EMIS 2025) - Seyed Mohammadreza Ghadiri; Sri Devi Ravana; Mohd Johari Mohd Yusof; Shamzani Affendy Mohd. Din (Atlantis Press International BV, 2025)
This is an open access book. 2025 4th International Conference on Engineering Management and Information Science (EMIS 2025) aims to bring together researchers, practitioners, and industry experts from diverse fields to discuss the latest advancements and trends in engineering management and information science. Building on the success of its previous editions, EMIS 2025 will continue to foster an interdisciplinary platform that encourages collaboration and knowledge sharing among participants. With rapid technological advancements and the increasing complexity of engineering projects, this conference provides an essential forum for addressing the challenges and opportunities faced in the contemporary landscape. Attendees will gain valuable insights, explore cutting-edge research, and network with peers to establish connections that can lead to innovative solutions and collaborations in the future. EMIS 2025 will cover a wide range of topics pertinent to engineering management and information science, including but not limited to: project management methodologies, data analytics in engineering, risk management, supply chain optimization, and the impact of artificial intelligence on engineering practices. Additionally, the conference will explore the role of sustainability in engineering management, innovative practices in information systems, and the implications of emerging technologies in various engineering fields. We invite original research papers, case studies, and panel discussions that contribute to the ongoing discourse in these areas. Our aim is to highlight best practices and innovative approaches that can drive performance and efficiency in engineering and management sectors. EMIS 2025 distinguishes itself from previous editions by incorporating a more robust focus on practical applications of emerging technologies in engineering management and a greater emphasis on sustainability. This year, we will feature specialized workshops and interactive sessions that allow participants to engage in hands-on experiences, fostering deeper learning and collaboration. Additionally, the conference will include keynote speeches from prominent leaders in the field who will share their insights on the future of engineering management and information systems. Our commitment to inclusivity will be reflected in a wider range of topics and a richer diversity of speakers and participants, ensuring that all voices are heard and represented in the discussions. This evolution aims to enhance the conference experience, making it more relevant and impactful for all attendees.